2014
DOI: 10.1186/1472-6920-14-140
|View full text |Cite
|
Sign up to set email alerts
|

Female residents experiencing medical errors in general internal medicine: a qualitative study

Abstract: BackgroundDoctors, especially doctors-in-training such as residents, make errors. They have to face the consequences even though today’s approach to errors emphasizes systemic factors. Doctors’ individual characteristics play a role in how medical errors are experienced and dealt with. The role of gender has previously been examined in a few quantitative studies that have yielded conflicting results. In the present study, we sought to qualitatively explore the experience of female residents with respect to med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(66 citation statements)
references
References 23 publications
1
64
0
1
Order By: Relevance
“…In line with this, a qualitative study reported mitigation of responsibility, normalizing the incident, and blaming the system as defensive attitudes (Mankaka et al. ). To cope with the ordeal, rationalizing was also used (Pinto et al.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…In line with this, a qualitative study reported mitigation of responsibility, normalizing the incident, and blaming the system as defensive attitudes (Mankaka et al. ). To cope with the ordeal, rationalizing was also used (Pinto et al.…”
Section: Resultsmentioning
confidence: 92%
“…Three studies agreed that female healthcare workers experienced greater intensity of emotions than male healthcare workers (Mankaka et al. ; McLennan et al. ; Mira et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations